Предмет: Алгебра,
автор: natashaarod44
-5(х-3)+2х=3(х+10)-х
обьясните как решить
Ответы
Автор ответа:
2
Ответ:
x = -3
Объяснение:
-5(х - 3) + 2х=3(х + 10) - х
-5x + 15 + 2x = 3x + 30 - x
-3x - 2x = 30 - 15
-5x = 15
x = -3
Автор ответа:
2
-5(х-3)+2х=3(х+10)-х
-5х+15+2х=3х+30-х
-3х+15=2х+30
-3х-2х=30-15
-5х=15
х=15:(-5)
х=-3
Похожие вопросы
Предмет: Русский язык,
автор: Love777333
Предмет: Українська мова,
автор: tarascem
Предмет: Русский язык,
автор: kuzneczovak
Предмет: Физика,
автор: vladmutar200
Предмет: Геометрия,
автор: Аноним